Control of molecular structure in the generation of highly luminescent liquid crystalline perylenebisimide derivatives: synthesis, liquid crystalline and photophysical properties - Jancy, B.; Asha, S. K. (Journal of Physical Chemistry B, 2006)
We report here, for the first time, the role of the molecular design on the liquid crystalline and solid-state photoluminescent properties of soluble and thermally stable liquid crystalline perylenebisimide derivatives. A new series of perylenebisimides were designed and developed for this purpose by adopting the stoichiometry-control approach, and amine-, hydroxyl-, ester-, and amide-functionalized molecules were synthesized. Various types of spacers with different lengths (C2 to C12), types (linear, cyclohexyl, and tricyclodecane), and end-capped by phenyl or tridodecyloxy gallic units were introduced in the perylenebisimide core. The molecules were completely characterized by NMR, FT-IR, SEC, and MALDI-TOF mass techniques. Thermal analysis revealed that the perylenebisimide derivatives were thermotropic liquid crystalline, and threadlike nematic phases were observed under a polarizing light microscope. The spacer length and the rigidity of the spacers play a major role in the liquid crystalline properties of the materials. In phenyl systems, the C6 chain with ester- and the C12 chain with amide-end-capped molecules showed a nematic phase, whereas the C6 chain with an amide end cap and their cyclic and tricyclic counterparts did not show any LC property. The introduction of a tridodecyloxy gallic unit induced the LC property in C12 and the cyclohexyl system; however, it failed to do so in the tricyclodecane molecule. The absorption properties of the molecules were almost unchanged by the structural variation; however, the emission quantum yield in solution and photoluminescent (PL) intensity in the solid state were significantly different. Though the gallic unit induced liquid crystallinity in the perylenebisimide core, the quantum yield and PL intensity are 4−5 times less compared to those of the simple phenyl-capped liquid crystalline system. Among the various types of spacers, the tricyclodecane induced strong molecular aggregates via π-stacking, which in turn increased the rigidity of the entire perylenebisimide core, resulting in the absence of liquid crystallinity and low luminescence compared to their linear and cyclohexyl analogues. The molecular aggregates were very stable even at very dilute concentration and also at high temperatures. The aggregates disappeared immediately upon addition of trifluoroacetic acid, thus confirming the strong hydrogen bonding in the aggregated states. In a nutshell, the present report demonstrates the importance of molecular design for introducing liquid crystalline phases in perylenebisimides and also the development of novel highly luminescent n-type π-conjugated material for application in optoelectronics.

Correlation of architecture with excimer emission in 100% pyrene-labeled self-assembled polymers - Kaushlendra, K.; Deepak, V. D.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2011)
Pyrene was incorporated as pendant unit to side-chain urethane methacrylate polymers having a short ethyleneoxy or a long polyethyleneoxy spacer segment. The short-spacer pyrene urethane methacrylate was also incorporated either as block or random copolymer (1:9) along with polystyrene. The excimer emission was observed to be different for different polymers with the random copolymer exhibiting the lowest efficiency. But, the total quantum yield was highest (phi = 0.58) for random copolymer due to the high emission coefficient of monomer compared to that of excimer. The polymer dynamics were compared by steady state emission and fluorescence decay in THF or THF/water (9:1) solvent mixture and films. The solid state decay profile showed decay without a rise time indicating presence of ground state aggregates. In THF/water (9:1), the decay profile at the excimer emission (500 nm) showed a rise time indicating dynamic excimers. The evolution of excimeric emission centred similar to 430 or similar to 480 nm as a function of temperature was also studied in THF/water (9:1). The I(E)/I(M) ratio for the lambda(343) nm excitation exhibited steady increase with temperature with the block copolymer PS-b-PIHP exhibiting the highest ratio and highest rate of increase; whereas, the random copolymer PS-r-PIHP had the lowest I(E)/I(M) ratios. (C) 2011 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 49: 1678-1690, 2011
Keywords: I(E)/I(M) ratio; Morphology; pyrene; Self-assembly; structure-property relations; time-resolved and variable temperature fluorescence

Charge storage and electron transport properties of gold nanoparticles decorating a urethane-methacrylate comb polymer network - Patil, Sumati; Datar, Suwarna; Rekha, N.; Asha, S. K.; Dharmadhikari, C. V. (Nanoscale, 2013)
We propose enhanced charge storage capacity of nanoparticles based polymer films. A flat band voltage window varying from 5-7 V is obtained leading to a trapped charge density of the order of 10(13) cm(-2). These results vary for two distinct morphologies obtained due to decoration of a urethane-methacrylate comb polymer (UMCP) network by gold nanoparticles (AuNPs). Films have been further investigated for morphology, optical, charge storage, and electron transport properties using techniques like scanning electron microscopy (SEM), atomic force microscopy (AFM), absorption spectroscopy (UV-Vis), scanning tunneling microscopy/spectroscopy (STM/STS) and capacitance versus voltage (C-V) measurements. SEM and AFM confirm either the deposition of AuNPs inside the UMCP network or the formation of ring like structures depending on the deposition sequence. STS measurements performed on both films are compared with bare UMCP and AuNPs films. Current versus voltage (I-V) characteristics so obtained are discussed in the light of electron transport mechanisms in such materials.

Chiral poly(L-lactic acid) driven helical self-assembly of oligo(p-phenylenevinylene) - Nisha, S. Kumari; Asha, S. K. (Journal of Materials Chemistry C, 2014)
The synthesis and self-assembly of a series of copolyesters incorporating varying mol ratios of an achiral oligo(p-phenylenevinylene) (OPV) into the backbone of a chiral poly(L-lactic acid) (PLLA) via high temperature solution blending is reported. The polymers were characterized by H-1 NMR spectroscopy and size exclusion chromatography (SEC) and their bulk properties were investigated by differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (WXRD). The DSC and WXRD analyses confirmed the crystallinity and pi-pi stacking of the OPV units in the PLLA-OPV copolyester. Absorption, emission and lifetime-decay studies showed that the OPV chromophore was highly aggregated in the solid state. The solid powder samples of the copolyesters exhibited an intense, red shifted aggregate emission beyond 470 nm. Circular dichroism (CD) spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM) studies revealed that the PLLA-OPV copolyester formed a self-assembled architecture, in which the helical organization of the achiral OPV segments was dictated by the chiral PLLA segments. The observed CD signal and AFM image accounted for the right-handed helical self-assembly of the OPV chromophore in the solid state. These results confirmed the effect of the chiral PLLA segment on tuning the OPV chromophore packing and supramolecular chirality in molecular aggregates. The methodology illustrated here provides opportunities for the design of a new class of hierarchical, self-assembled architectures, based on organic pi-conjugated materials and the manipulation of their optical properties.

Carbohydrate-based polyester and amino acid polyester photocrosslinker and their resin formulation for 3D printing applications - Kamble, Ganesh N.; Joshi, Dheeraj Chandra; Gavhane, Utreshwar A.; Asha, S. K. (Chemistry-An Asian Journal, 2025)
Fully bio-based polyester was designed and synthesized using the carbohydrate-based diol 2,4:3,5-di-O-methylene-D-mannitol (Manx) and dimethyl ester of 2,3:4,5-di-O-methylene-galactaric acid (Galx). Photocurable resin formulations were prepared by incorporating up to 15 wt% of the carbohydrate polyester into hydroxyl ethyl methacrylate (HEMA) along with polyacrylamide crosslinker derived from L-glutamic acid. Complex 3D structures with good shape fidelity could be 3D printed using these novel polyester resin formulations. The incorporation of the carbohydrate polyester improved the glass transition temperature of the 3D-printed objects. Enzymatic erosion studies conducted using esterase enzyme revealed a higher degradation rate for the 3D-printed films containing the carbohydrate polyester. The hydrolytic degradation analysis conducted in both acidic and basic environments revealed that the 3D-printed polymer network exhibits stability and resilience in acidic conditions, while it undergoes complete degradation in basic conditions. This finding underscores the possibility of tailoring degradation processes under regulated circumstances.
Keywords: 3D printing; Amino acid; Carbohydrate polyester; Enzymatic degradation; Resin formulation